Impacts of the Fukushima Nuclear Accident on Fish and Fishing Grounds - Nakata, Kaoru; Sugisaki, Hiroya; Nakata, Kaoru; Sugisaki, Hiroya (Cham Springer Nature, 2015)
Fish & Wildlife Biology & Management; Ecology; Environmental Monitoring/Analysis
English
Keywords: Management of specific areas; Fisheries & related industries; Fish & Wildlife Biology & Management; Ecology; Environmental Monitoring/Analysis